Evaluation of dental parameters perception by Lebanese prosthodontists, orthodontists and aesthetic doctors - Celine KAMEL; Nadine NACHABÉ; Nada EL OSTA; Carina MEHANNA ZOGHEIB (International Arab Journal of Dentistry (IAJD), 2020)
The aim of this study was to compare the effect of varying smile parameters with respect to three indices between Lebanese dentists (prosthodontists and orthodontists) and medical doctors. 245 participants were divided into 3 groups. A photograph of the smile that conforms to a woman’s aesthetic standards has been digitally altered to provide a reference image. Next, images where modified then evaluated. The collected data was analyzed. Dental professionals critically judged dental aesthetics by focusing on the gingivo-dental characteristics that make the smile less pleasant. Dental professionals detected minimal dental discrepancies in a smile, unlike doctors who assessed the smile in relation to the entire face since their judgment is global. Lebanese doctors have a different perception of oral aesthetics from Lebanese prosthodontists and orthodontists.